GROSSI, Miriam; LAGO, Mara; NUERNBERG, Adriano (Org.). Estudos in(ter)disciplinados: gênero, feminismo, sexualidade. - Rodrigues, Laís Oliveira; Scott, Russell Parry (Revista Estudos Feministas, 2013)
GROSSI, Miriam; LAGO, Mara; NUERNBERG, Adriano (Org.). Estudos in(ter)disciplinados: gênero, feminismo, sexualidade.